Studies of Laboulbeniales on Myrmica ants (III): myrmecophilous arthropods as alternative hosts of Rickia wasmannii - Pfliegler Walter P.; Báthori Ferenc; Haelewaters Danny; Tartally András (Parasite, 2016)
Myrmecophilous arthropods and their manifold relations to host ants are interesting from an evolutionary perspective. Rickia wasmannii is an ectoparasitic fungus belonging to the Laboulbeniales order. Here, we show that inquiline mites can become infected by R. wasmannii, which was thought to be restricted to the genus Myrmica (Hymenoptera: Formicidae). This is the first report of R. wasmannii from an alternative host in another subphylum (Chelicerata). We also found immature fruiting bodies on a larva of Microdon myrmicae (Diptera: Syrphidae), which represents the first report of any Rickia species on flies. This fungus is capable of infecting alternative, unrelated host species as they co-occur in the ant nest “microhabitat”. These observations provide direct evidence for ecological specificity in Laboulbeniales. The presence of R. wasmannii on inquilines in Myrmica ant nests suggests that the parasite may have adapted to the ant nest environment and is less dependent on acquiring specific nutrients from the hosts. However, the alternative cannot be excluded; these infections might also represent chance events if the fungus is incapable of fulfilling its life cycle.